Selection of coal transportation mode from the open pit mine to the thermic power plant using Fuzzy Analytic Hierarchy Process - Özfirat, Pinar Mizrak; Özfirat, Muharrem Kemal; Malli, Tahir (Transport, 2018)
Coal produced in open pit mines should be moved to thermic power plants for production of power. Thermic power plants require very large amounts of coal. In transportation process of this coal, both costs and technical parameters should be considered. Common alternative transportation modes in this process are belt conveyors, truck types, suspension rail conveying systems, pipelines and railways. Selection of one of these modes is influenced by transportation distance, inclination of the haulage road, amount of coal reserve, investment costs, production capacity and unit production cost of the open pit mine. In this study, advantages and disadvantages of alternative transportation modes are analysed using Fuzzy Analytic Hierarchy Process (F-AHP). The results revealed, belt conveyors and trucks transportation by are superior to others.First published online 12 April 2017